Progress in Bolivia: Declining the United States Influence and the Victories of Evo Morales. Issue 4 (December 2016) - Pineo, Ronn
This article provides an assessment of economic and social progress in Bolivia under Evo Morales. An examination of the leading factors that explain Bolivia's turn to the left is offered, focusing on how the US policies and actions contributed to the collapse of the old regime. The social and economic policy directions since Morales assumed office is presented, followed by a discussion of the process of creating a Bolivian understanding of democracy, one that is deeper and richer than the nation has experienced heretofore.